Analisis Laporan Keuangan PT Indofood Sukses Makmur Tbk Tahun 2024 - 2025: Analysis of Financial Statements of PT Indofood Sukses Makmur Tbk Year 2024 - 2025 - Sri Hermuningsih; Muh Furqan Ramli; Nurika Dwi P; Ayu Dewi (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the financial performance of PT Indofood Sukses Makmur Tbk during the 2024–2025 period using liquidity, solvency, activity, and profitability ratios. As a company with an integrated vertical business model, Indofood holds a strategic position in maintaining supply stability and production efficiency amid economic fluctuations. The research method employed is a quantitative descriptive analysis of the company’s balance sheets and income statements. The analysis results indicate that the company is in a very healthy and stable financial condition. Liquidity levels have improved, with the Current ratio reaching 4.15% in 2025, signaling a very strong capacity to meet short-term obligations. In terms of solvency, the company successfully mitigated debt risk by reducing the Debt-to-Equity Ratio to 84%, reflecting an increasingly self-reliant capital structure. Profitability also showed a positive trend, with the Net Profit Margin rising to 15%. However, this study found a decline in efficiency in activity ratios, particularly in accounts receivable and inventory turnover, which have tended to slow down. Therefore, the company is recommended to re-optimize current asset management and tighten collection policies to maintain sustainable cash flow.